Occupational stress, anxiety and depression among Egyptian teachers - Dalia Desouky; Heba Allam (Springer, 2017)
Abstract Occupational stress (OS) among teachers predispose to depression and anxiety. No study was done to assess these problems among Egyptian teachers. This study aimed to assess the prevalence of OS, depression and anxiety among Egyptian teachers. A cross sectional study was done on 568 Egyptian teachers. The respondents filled a questionnaire on personal data, and the Arabic version of the Occupational Stress Index (OSI), the Arabic validated versions of Taylor manifest anxiety scale and the Beck Depression Inventory (BDI) were used to assess OS, anxiety and depression respectively. The prevalence of OS, anxiety and depression among teachers was (100%, 67.5% and 23.2%) respectively. OS, anxiety and depression scores were significantly higher among teachers with an age more than 40 years, female teachers, primary school teachers, those with inadequate salary, higher teaching experience, higher qualifications and higher workload. A significant weak positive correlation was found between OS scores and anxiety and depression scores. This study indicated the need for future researches to address risk factors of OS and mental disorders among Egyptian teachers, and the need of periodical medical evaluation of teachers and medical and psychological support for the identified cases.